Topologies for Battery and Supercapacitor Interconnection in Residential Microgrids with Intermittent Generation - Narvaez Cubillos, Eider Alexander; Cortés Guerrero, Camilo Andrés; Trujillo Rodríguez, Cesar Leonardo (Ingeniería, 2020)
Context:This paper presents a comparative study of the performance of three topologies for interconnecting Lithium ion batteries and supercapacitors in a hybrid energy storage system for use in electric residential microgrids with intermittent generation. The hybrid system’s main purpose is to prolong battery life, using the supercapacitor to handle the dynamic component of current from a pulsed current load. This work builds upon a preliminary simulation-based study, in which two semi-active topologies were compared and evaluated. Here, we add an active topology to the study and describe the operational benefits of each topology. Method:For every topology in this study, a non-isolated half-bridge bidirectional DC converter was used, and a proportional–integral (PI) double-loop linear ACC control algorithm was designed for controlling the converters. In the active topology an additional optimisation-based real-time frequencydecoupling control strategy was employed. Results:A parallel active topology allows better management of stored energy in the SC by supporting variation of SC terminal voltages with a DC converter as interface to the DC bus. Conclusions: Semi-active topologies are easier to design and control, but the operational benefits of supercapacitors require voltage variation at the terminals. This variation is made possible with an active topology. Acknowledgements: First author thanks Universidad Distrital Francisco Jos´e de Caldas for the financial support in his doctoral studies through the study commission contract N° 000101-2016.